A new paradigm is needed to guide the utility of functional electrical stimulation in rehabilitation medicine - Gad Alon (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2020)
Back in 2006, an invited commentary raised the question "are we asking clinically relevant questions"? The commentary referenced an application of electrical stimulation in a clinical trial [1]. This question regarding Neuromuscular Electrical Stimulation (NMES) and Functional Electrical Stimulation (FES) is as relevant in 2020. Based on the premise and presumption that the aim of applying NMES/FES is to enable each patient achieve the most effective and efficient recovery of functional independence, one must wonder if we are asking the most critical, yet clinically relevant questions? This perspective focuses on locomotion and upper extremity function following a Cerebrovascular Accident (CVA) and non-neurological damage to the knee joint. It delineates several questions elaborating on the issue of meaningful outcomes to the patients versus the focus of clinician and researchers on measurable outcomes. It offers pathways that should hopefully lead to considerably more effective and efficient utilization of NMES and FES in rehabilitation medicine.